HUBUNGAN DURASI DUDUK DAN FAKTOR INDIVIDU DENGAN KELUHAN LOW BACK PAIN MAHASISWA KESEHATAN MASYARAKAT UPN VETERAN JAKARTA SELAMA PEMBELAJARAN JARAK JAUH - Siti Nafisah Sofiyanti (2021)
Sitting duration during online learning has become one of the factors of most student complained about. Low back pain is pain in the lower back caused by activity that exceeds the capacity of a person's body. The objectives of this research was to know the relation between sitting duration and individual factor with low back pain in public health students UPN Jakarta during online learning. This was a quantitative research which used the design of cross-sectional study with 237 student samples of Public Health Students. The sampling technique of this research has used a proportianate stratified sampling. The results of this study indicated factors that related with LBP complaints which are sitting duration (p-value = 0.003; OR = 4.9) and (stress) psychology (p-value = 0.005; OR = 3.8). Therefore, the writer suggested the students to strech every 20 minutes and manage stress better.